Direction-based urban broadcast protocol for vehicular ad hoc networks. (2018) - Li, Gui-Sen; Chen, Xu-Hui; Wu, Ke-Shou; Chen, Ren
Multi-hop broadcast for vehicular ad hoc networks in urban environments is a difficult task for the impact of the intersections. The forward of the next relay will face the problem that some branches of the intersection will not be covered in time. In this paper, we propose a novel broadcast protocol for urban environments. The proposed protocol considers the transmission direction of broadcasting message and the moving direction of forwarding vehicle for delivering the message over the intersection. It delivers the message to all road directions at the intersection by an efficient and fast way. Using the direction information, an agent vehicle mode also has been proposed to cope with the disconnected problem. Performance evaluation results show that the proposed protocol improves the reachability and speeds up the broadcast process.